Opioid Exposures Reported to U.S. Poison Centers. (27th May 2021) - Rege, Saumitra V.; Smith, Moira; Borek, Heather A.; Holstege, Christopher P.
Abstract: Objective: Opioid-related deaths are a leading cause of accidental deaths in the United States (U.S.). This study aims to examine the national trends in opioid exposures reported to U.S. poison centers (PCs). Methods: The National Poison Data System (NPDS) was queried for opioid exposures between 2011 and 2018. We descriptively assessed the demographic and clinical characteristics. Trends in opioid frequencies and rates were analyzed using Poisson regression. Independent predictors of serious adverse events in opioid exposures were studied. Results: There were a total of 604, 183 opioid exposure calls made to the PCs during the study period. The frequency of opioid exposures decreased by 28.9% (95% CI: −29.6%, −28.1%; p < 0.001), and the rate of opioid exposures decreased by 21.2% (95% CI: −24.7%, −16.9%; p < 0.001). Multiple substance exposures accounted for 48.9% cases. The most frequent age group was 20–29 years (19.3%). Suspected suicides accounted for 34.9% cases. There were 7, 246 deaths in our study sample, with 6.8% of cases demonstrating major effects. Hydrocodone was the most frequently observed opioid causing a toxic exposure and naloxone was used in 20.6% cases. Important predictors of a serious adverse event were age, gender, multi-substance exposures, and reasons for exposure. Conclusions: Analysis of calls to PCs indicated a decreasing trend of opioid exposures. However, the proportion of SAEs due to such exposures increased. There was a high proportion of intentional exposures and occurred in older age groups. PCs are a vital component of real-time public health surveillance of overdoses in the current opioid crisis.